International Remittances and Subjective Wellbeing in Sub-Saharan Africa: A Micro-level Study - Sulemana, I.; Doabil, L.; Anarfo, E.B. (Journal of Family and Economic Issues, 2019)
According to United Nations reports, in 2017, there were about 24.6 million Africans living outside of Africa. As a corollary, remittances to the continent have increased tremendously, exceeding official development assistance. The present paper examined whether receiving international remittances is correlated with the subjective wellbeing of relatives left behind in Africa. Using data from the Round 6 of the Afrobarometer Surveys in 32 Sub-Saharan African countries, our results from ordinary least squares, instrumental variable two-stage least squares, ordered probit, and instrumental variable probit regressions revealed unambiguously that receiving remittances exert a positive and statistically significant effect on subjective wellbeing at the 0.1% level. Specifically, we found that a unit increase in the frequency with which people receive remittances is associated with a 0.0660-point increase in subjective wellbeing, ceteris paribus. Moreover, a unit increase in receiving remittances increases the probability that the respondent would report having good and very good living conditions by about 1.67% and 0.44%, respectively. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Living conditions; Migration; Remittances; Sub-Saharan Africa; Subjective wellbeing